Let$1 (Bs find out about toothpastes - Barabas, Kathy, 1945-; Williams, John, 1963-; Sasaki, Ellen Joy (New York : Scholastic Inc., 1997)
Illustrations and simple text describe the process of making toothpaste, from combining the raw ingredients to shipping the packaged tubes to the store.
Keywords: Toothpaste -- Juvenile literature; Toothpaste; Manufactures